THE SOCIAL - ECONOMIC AND CULTURAL CHARACTERISTICS OF THE ROMANIAN - BELGIAN RELATIONSHIPS - Cristina-Maria, PESCARU (Strategii Manageriale, 2014)
Belgium may be, for some of the Romanians, an experience outside the home country borders. The adaptation is done in time, for each one, it matters very much how you got in the destination country. The circumstances and knowledge of the host country language are essential for adaptation. It's very important to be recommended both to the individuals and to those working in institutions, associations etc.